The Behavioral Responses of the Employees and the Ways of Improvement While Facing Changes in the Organization - Hovhannisyan, Arevik; Simonyan, Aramayis («Տնտեսագետ» հրատ․)
This work aims to study the process of changes in organizations and the multi-layered relationships that arise in them. Since the implementation of changes infers a certain change in the behavior of employees, the article puts forward certain factors that can determine the reaction of employees in the process of changes, implying such behavioral manifestations as support and resistance. Using the SPSS software package, the behavior of the employees of the "Teach for Armenia" organization during the implementation of changes was studied, hypotheses were put forward based on previously created factors, which were confirmed due to descriptive and correlational analyses. As a result of the analysis, appropriate conclusions were made. The paper also touches on the key directions for improving the employees’ behavior, which is reflected in the section of conclusions. On the basis of some recommendations the organization's current experience is studied. Some organizations have already had successful experience, and some of them are related to such directions of behavioral improvement of employees, such as the formation of a package of effective habits.
Keywords: Management